In the Red Corner: The Marxism of José Carlos Mariátegui - Fontes, Yuri Martins (Labour / Le Travail, 2021)
The article reviews the book, "In the Red Corner: The Marxism of José Carlos Mariátegui," by Mike Gonzalez.